Submission, peace and happiness: heal the soul, prosper the society - Abdullah, Fatimah (2010)
Islam provide a certain and sure goal in man's process of freeing himself. Freedom is the successful struggle of subjugating the animal soul; it is directed to the attainment of supreme peace, and pacified soul, al-nafs al-mutmai'inah. This struggle throughtout man's life is a continuous EbEdah, one continuous confirmation of his obedience to God. It is a continuous process to fulfill the purpose of his creation and existence, to return his self to the Owner. A concept of freedom such as this would have no conflicting problems with the bidding of the Divine Law. This is so because, real freedom from any obstacles of worldly life can only be attained through the realization of fitrah; and the realization of fitrah cannot be attained without submission to God and obedience of the laws and teachings of his prophet. Thus, obedience to God's law, instead of hindering one's freedom is in fact the only "one way" road to attaining it, and to securing happiness in this world and hereafter. Happiness thus turns out to be an important experiential phenomenon which, according to the Qur'an can never fully realized without submission, understood in the true sense. Such a life of obedience (submission) shall bring in peace to the heart and will in turn establish real peace and prosperity in society at large. Islam as submission to God id the only way, which makes the person, feels at peace with God, with himself and his environment. This article attempts to highlight the relationship between submission, peace or freedom of the self and happiness.